Análise de manifestações patológicas em estruturas de concreto armado: estudo de caso em uma obra pública paralisada na cidade de Macapá-AP - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá, 2024)
It is common to come across unfinished concrete structures, resulting from abandonment or interruption of construction projects. These structures may suffer from various pathological manifestations that affect their performance and durability. Pathological manifestations are problems that manifest in the structure resulting from failures during the conception, construction, or use process. When dealing with stalled construction projects, the structure, which usually presents itself with exposed concrete, may not only carry flaws related to the construction process but also suffer from the actions of weather conditions that can exacerbate various other problems. In this scenario, this study aims to analyze a stalled construction project in the city of Macapá, identifying its pathologies, discussing possible causes, and proposing comprehensive solutions for the treatment of pathological manifestations. The methodology adopted consists of descriptive research, involving a literature review that provides the theoretical basis for the research and field survey that allows the identification and documentation of pathologics present in the stalled construction project. The diagnostic method proposed by Lichtenstein (1986), which consists of the stages of gathering information, diagnosing the situation, and defining the conduct, is applied to determine the causes of pathologies and propose suitable solutions. The data obtained in the field survey are analyzed from two perspectives, through quantitative analysis and qualitative analysis. Through quantitative analysis, an attempt is made to provide an overview of the state of the construction project, showing the incidence of the main manifestations in each structural element. In qualitative analysis, the possible causes for the emergence of each identified pathological manifestation are discussed, proposing a treatment suggestion. Remarkably, it was observed that the incidence of mold is practically generalized throughout the structure, while phenomena such as cracks, reinforcement corrosion, and disintegration also have a high occurrence, followed by efflorescence, humidity, segregation, and disintegration present in a significant portion of structural elements. Thus, the results obtained corroborate the initial hypothesis of the work, suggesting that pathological manifestations are the result of the structure's exposure to weather conditions or construction process failures.
Keywords: Construção civil - Diagnóstico estrutural; Estruturas de concreto armado; Construção civil - Diagnóstico estrutural; CNPQ::ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL; ODS 11 – Cidades e comunidades sustentáveis; ODS 12 – Consumo e produção responsáveis; ODS 9 – Indústria, inovação e infraestrutura